“The prettiest and most soulfull flag—in all of Canada”: A History of the Flag of Ontario - Hart, John (Ontario History)

(untitled) (The Ontario Historical Society, 2025)
This article offers the first published account of the origins of the Flag of Ontario. Proclaimed in May 1965, the Ontario provincial flag (like that of Manitoba) was a consequence of the preceding national flag debate. Sometimes dismissed as an act of rebellion against the new Canadian flag, the new provincial flag was largely welcomed by a receptive Ontario public. The loss of the Canadian Red Ensign, a long-respected and familiar symbol for much of English Canada, was deeply felt by many. Much of Ontario was ambivalent about changing the national flag and the adoption of a provincial Red Ensign was held by some to be an act of compromise, easing the acceptance of the new Flag of Canada after a divisive national debate. This article also brings to light several less well-known, ultimately unsuccessful flag proposals for Ontario that arose in the early 1960s.